Estimated varicella incidence on the basis of a seroprevalence survey - MUÑOZ, M. P.; DOMÍNGUEZ, A.; SALLERAS, L. (Epidemiology and infection, 2001)
Varicella is a disease caused by varicella-zoster virus. It is transmitted via the respiratory route, is highly communicable and mainly affects young children. An effective vaccine is now available, whose routine use is advised by health authorities in the USA and which can prevent severe disease, although breakthrough infections do occur. In deciding whether or not to include a vaccine in the routine vaccination schedule, knowledge of the morbidity of the disease in question is fundamental. Although reporting of varicella is compulsory in Catalonia, doctors only have to report the weekly number of cases diagnosed, and not their age distribution. Given that recent data on the prevalence of the infection in Catalonia according to age groups is available, it was considered that, using these data, an estimation of age-related incidence could be made. The objective of the present study was to estimate the incidence of varicella in Catalonia on the basis of the available seroprevalence data. A curve was fitted to the observed prevalence and point prevalence estimates for all ages were obtained. The incidence was derived by smoothed prevalence for each of these age groups. Estimated variance of the estimated incidence was obtained by the delta method. Predicted prevalence in the 0–4 years age group was calculated by the smoothed prevalence. The model that best fitted the sample prevalence was the exponential function. The estimated number of varicella cases in this study was 46419 (95% CI 40507–52270). As the population in Catalonia in 1996 was 6090040, the previous results give an incidence rate of 762·2 per 100000 persons/year with their 95% CI (666·1–858·3). The method described may be applied to the study of incidence rates in relation to the prevalence of diseases if we accept that the infection produces permanent immunity; the risk of mortality is the same for infected and non-infected subjects and that the disease incidence and population remain constant in time.